2014
DOI: 10.17017/jfish.v2i1.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diseases on fish production of baors in Jessore, Bangladesh

Abstract: The study was carried out to assess the impact of diseases on fish production in baors of Jessore district, Bangladesh from March 2012 to January 2013. Studied baors were selected randomly from each sub-district which covered 39.22% of total baors and 71.87% baor areas in Jessore district. All the surveyed baors were affected more or less by various diseases and in 80% baors noticeable production loss occurred almost every year. The main diseases were epizootic ulcerative syndrome (EUS), dropsy, gill rot and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Nonetheless, EUS seemed to emerge as the pre-dominant hazard, causing particularly large outbreaks until approximately the years 1998-99. In more recent years, the existence of the EUS was still described, but the economic impact figures were lower compared to previous estimates thanks to lower rates of infection (Dey et al 2014;Faruk et al 2004).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, EUS seemed to emerge as the pre-dominant hazard, causing particularly large outbreaks until approximately the years 1998-99. In more recent years, the existence of the EUS was still described, but the economic impact figures were lower compared to previous estimates thanks to lower rates of infection (Dey et al 2014;Faruk et al 2004).…”
Section: Discussionmentioning
confidence: 91%
“…One study described livelihood impacts of carp disease, such as the reduction of the total average yearly income of 18.5% during an outbreak of EUS in 1999 (Brown and Brooks, 2002). Later studies in carp polyculture production reported a prevalence of EUS similar to other clinical syndromes such as dropsy, fin rot, gill rot and observed that production losses were stabilising (Dey et al, 2014;Faruk et al, 2004;Hasan et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that seasonal fish grow-out in temporary water-bodies is widely practised in South Asia and these locations could be classed in many cases as subsistence fisheries (19,20,21). Fish are either introduced or make their way into these water bodies and are harvested primarily when the water-bodies dry out towards the end of the dry season.…”
Section: Synclidopus Macleayanusmentioning
confidence: 99%
“…An investigation by the Food and Agriculture Organization of the United Nations (FAO) of an EUS outbreak in the Democratic Republic of the Congo identified that fish of the Clariidae, Channidae and Protopteridae families were of greatest concern due to their importance as food species and the fact that they are air breathing and can be readily transported live to market (18). EUS appears to readily cross land barriers as evidenced in its reported spread, likely to be human or bird assisted, to seasonal water bodies in India and Bangladesh (19,20,21). Kamilya and Baruah (3) and, more recently, Kar (4), have reviewed the long history of EUS since its first reported occurrence in Japan in 1971 and subsequent reports in Australia in 1972, across Asia in the 1980s and 1990s, in the United States of America (USA) in 1980, Africa in the mid-to-late 2000s, and most recently in Canada in 2010.…”
Section: Introductionmentioning
confidence: 99%